Apache Spark with Java learn Spark from a big data guru - W., Tao; Lee, James (Packt Publishing, 2018)
"This course covers all the fundamentals of Apache Spark with Java and teaches you everything you need to know about developing Spark applications with Java. At the end of this course, you will have gained an in-depth knowledge pf Apache Spark, general big data analysis and manipulations skills. With these new skills you'll be able to help your company to adapt Apache Spark for building a big data processing pipeline and data analytics applications. This course covers 10+ hands-on big data examples. You will learn valuable knowledge on how to frame data analysis problems as Spark problems. Together we will learn examples such as aggregating NASA Apache web logs from different sources; we will explore the price trend by looking at the real estate data in California; we will write Spark applications to find out the median salary of developers in different countries through the Stack Overflow survey data; we will develop a system to analyze how maker spaces are distributed across different regions in the United Kingdom, and much more."--Resource description page
Title from resource description page (Safari, viewed May 8, 2018)
Keywords: Spark (Electronic resource : Apache Software Foundation); Application program interfaces (Computer software); Java (Computer program language); Interfaces de programmation d'applications; Java (Langage de programmation); APIs (interfaces); Electronic videos